2020
DOI: 10.15585/mmwr.mm6932a1
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Substance Use, and Suicidal Ideation During the COVID-19 Pandemic — United States, June 24–30, 2020

Abstract: † Disorders classified as TSRDs in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) include posttraumatic stress disorder (PTSD), acute stress disorder (ASD), and adjustment disorders (ADs), among others. § Unpaid adult caregiver status was self-reported. The definition of an unpaid caregiver for adults was a person who had provided unpaid care to a relative or friend aged ≥18 years to help them take care of themselves at any time in the last 3 months. Examples provided included helping with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

144
2,155
41
60

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,386 publications
(2,400 citation statements)
references
References 6 publications
144
2,155
41
60
Order By: Relevance
“…no prior researchers who have evaluated the physical and mental health of adolescent athletes in the United States during the pandemic. [16][17][18] Before the school closures and sport cancellations during the 2019-2020 academic year, 18 000 US high schools offered interscholastic athletics programs. 19 Organized sport participation is recognized as having profound positive influences on the health and well-being of adolescent students.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…no prior researchers who have evaluated the physical and mental health of adolescent athletes in the United States during the pandemic. [16][17][18] Before the school closures and sport cancellations during the 2019-2020 academic year, 18 000 US high schools offered interscholastic athletics programs. 19 Organized sport participation is recognized as having profound positive influences on the health and well-being of adolescent students.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…In a recent study of U.S. adults, more than 40% of respondents reported adverse mental health or increased substance use in June, 2020. 8 Furthermore, research shows that participants in shelter in place or lockdown due to COVID-19 experienced increasing rates of suicide ideation as months passed, whereas participants not under these COVID restrictions did not. 9 Resultingly, experts in the field are publishing resources aimed specifically at treating suicide with the Collaborative Assessment and Management of Suicidality (CAMS) 10 and safety planning 11 through the lens of the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…The worldwide COVID-19 crisis has disrupted routines, imposed unprecedented physical distancing measures, and caused widespread unemployment and financial instability (Nicola et al, 2020). These concerns may destabilize patients with established mental disorders such as anxiety disorder and depression, substance abuse and suicidal ideation, or be associated with mental health problems in previously undiagnosed individuals (Czeisler et al, 2020;Salari et al, 2020). Czeisler and colleagues (2020) indicated that adults in the United States reported an increase in adverse mental health conditions related to COVID-19 such as anxiety, depression, and trauma/stressors related disorders such as post-traumatic stress disorder (PTSD).…”
Section: Introductionmentioning
confidence: 99%